2009
DOI: 10.1002/jsfa.3791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of formulated goats' milk on calcium bioavailability in male growing rats

Abstract: The diets containing 80% and 57% of goat milk protein as casein delivered increased calcium absorption compared to the diet containing no casein, suggesting a minimum level of casein is needed to optimize calcium absorption from goat milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The basal diet used in this study was modified to remove dairy protein from the formulation and replace this with beef protein, in order to prevent any confounding effects. The protein used in rodent diets was from several sources including egg albumin, goat milk, CM, and beef protein [22][23][24]. With respect to milk composition, the data presented (Table 2) are consistent with the expected nutritional composition for both SM and CM as reported in the literature [25].…”
Section: Diet Compositionsupporting
confidence: 79%
“…The basal diet used in this study was modified to remove dairy protein from the formulation and replace this with beef protein, in order to prevent any confounding effects. The protein used in rodent diets was from several sources including egg albumin, goat milk, CM, and beef protein [22][23][24]. With respect to milk composition, the data presented (Table 2) are consistent with the expected nutritional composition for both SM and CM as reported in the literature [25].…”
Section: Diet Compositionsupporting
confidence: 79%
“…Importantly, goat milk formula performs similarly to cow milk formula, supporting infant growth and development in animal and human studies. Animal studies have shown goat milk to enhance the utilisation and retention of protein [ 53 , 54 ], mineral absorption and tissue storage (including calcium [ 55 , 56 ] and iron [ 56 , 57 , 58 ]), and intestinal fat absorption [ 59 ] as compared to cow milk. Randomised clinical trials in infants show the growth curves of children exclusively fed goat milk formula are similar to both breastmilk fed infants [ 60 ] and those fed cow milk formula [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of milk including cow and goat milk has long been known to have beneficial effects in relation to mineral absorption. McKinnon et al . assessed the effect of goat milk in a growing rat model using a ”fortified” formula milk containing different levels of goat milk derived caseins.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The consumption of milk including cow and goat milk has long been known to have beneficial effects in relation to mineral absorption. McKinnon et al [17] assessed the effect of goat milk in a growing rat model using a "fortified" formula milk containing different levels of goat milk derived caseins. The consumption of casein from goat milk significantly improved the calcium absorption of the rats (measured as fractional calcium absorbed) when compared to rats fed casein free formula.…”
Section: Introductionmentioning
confidence: 99%